Sources and transmission routes of campylobacteriosis: A combined analysis of genome and exposure data. Issue 2 (February 2021) - Mughini-Gras, Lapo; Pijnacker, Roan; Coipan, Claudia; Mulder, Annemieke C.; Fernandes Veludo, Adriana; de Rijk, Sharona; van Hoek, Angela H.A.M.; Buij, Ralph; Muskens, Gerard; Koene, Miriam; Veldman, Kees; Duim, Birgitta; et al.
Highlights: Human campylobacteriosis cases mostly originate from poultry and cattle. Pets and surface water are important non-livestock sources of campylobacteriosis. Risk factors for campylobacteriosis differ according to the original reservoirs. Effects of frequency and alternative pathways of exposure are significant. WGS and epidemiological data analyses unveil the origins of campylobacteriosis. Summary: Objectives: To determine the contributions of several animal and environmental sources of human campylobacteriosis and identify source-specific risk factors. Methods: 1417 Campylobacter jejuni / coli isolates from the Netherlands in 2017–2019 were whole-genome sequenced, including isolates from human cases ( n  = 280), chickens/turkeys ( n  = 238), laying hens ( n  = 56), cattle ( n  = 158), veal calves ( n  = 49), sheep/goats ( n  = 111), pigs ( n  = 110), dogs/cats ( n  = 100), wild birds ( n  = 62), and surface water ( n  = 253). Questionnaire-based exposure data was collected. Source attribution was performed using core-genome multilocus sequence typing. Risk factors were determined on the attribution estimates. Results: Cases were mostly attributed to chickens/turkeys (48.2%), dogs/cats (18.0%), cattle (12.1%), and surface water (8.5%). Of the associations identified, never consuming chicken, as well as frequent chicken consumption, and rarely washing hands after touching raw meat, were risk factors for chicken/turkey-attributable infections. Consuming unpasteurized milk or barbecued beef increased the risk for cattle-attributable infections. Risk factors for infections attributable to environmental sources were open water swimming, contact with dog faeces, and consuming non-chicken/turkey avian meat like game birds. Conclusions: Poultry and cattle are the main livestock sources of campylobacteriosis, while pets and surface water are important non-livestock sources. Foodborne transmission is only partially consistent with the attributions, as frequency and alternative pathways of exposure are significant.